Kejadian malaria dan status gizi balita di Kabupaten Manokwari Provinsi Papua Barat - Therresse Nofianti (Jurnal Gizi Klinik Indonesia, 2014)
Background: The prevalences of severe acute malnutrition, moderate acute malnutrition and low birth weight (LBW) in West Papua Province is higher than the national prevalence. Malaria disease, especially in an infant, is also of concern in this province. Manokwari District is regarded as malaria endemic area due to the high morbidity rate in the entire district.Objective: To determine the incidence of malaria, nutritional status of children and to analyze the relationship between two of them.Method: The methodology that used in this research is cross-sectional design conducted in four health centers in Manokwari with a sample of 100 children aged two to five years. The data were analyzed using Chi-Square analysis and logistic regression analysis.Results: The incidence rate of malaria in Manokwari district is high. This is because the number of an infant that was infected highly and lowly by malaria do not vary much. Results show that 42% children suffering from severe malaria, particularly tropical malaria type, with a frequency of more than two times in six months so that it had a direct effect on appetite and weight. Average nutritional status based on weight/height and height/age is normal while according to weight/age is not normal. Infants with severe and moderate acute malnutrition are not found in this study.Conclusion: The incidence rate of malaria in children under five in the district of Manokwari is high, the nutritional status of children under five in the past are in the normal category and at the time of the study were not normal, this is due at the time of the study many infants experience pain and therefore contributes to the appetite that directly affects body weight of infants. Furthermore, it is known that there is a relationship between the incidence of malaria by the nutritional status of children in the district of Manokwari.